Pendeteksi Propagasi Menggunakan Metode FM Berbasis Personal Komputer - Jamal, Zaidir (Jurnal Informatika, 2010)
Generally, point to point communication and broadcasting uses VHF band, each function VHF band can use for observes   activities at ionosphere. This research designed and realized   propagation detection use frequency modulation based personal computer.  Results of the research are realization of system and simulation. Simulation results   before ionosphere reflection occur is  50 % and after ionosphere reflection occur is 90 %. Frequency modulation method can be implemented   earthquake detection with realized measurement stations. Keyword : VHF, Propagation, ionosphere